2013
DOI: 10.1590/s1413-70542013000300007
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds, methylxanthines and antioxidant activity in cocoa mass and chocolates produced from "witch broom disease" resistant and non resistant cocoa cultivars

Abstract: The "witch broom disease" caused by the fungus called Moniliophthora perniciosa is one of the most important cocoa diseases in Latin America, causing around 70% production reduction in the southern Bahia. In attempt to solve the problem, many cultivars resistant to the disease have been recommended to farmers. On the other hand, the chocolate flavour is composed by many compounds whose formation depends on the genetic background, environment where cocoa is grown and processing operations. Therefore, this work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Results showed higher epicatechin content than catechin and higher theobromine content than caffeine, as was also reported by Leite et al (2013) who studied cocoa mass and Carrillo et al (2014) who studied sun-dried cocoa beans.…”
Section: Resultssupporting
confidence: 83%
“…Results showed higher epicatechin content than catechin and higher theobromine content than caffeine, as was also reported by Leite et al (2013) who studied cocoa mass and Carrillo et al (2014) who studied sun-dried cocoa beans.…”
Section: Resultssupporting
confidence: 83%
“…Many authors reported the highest levels of (-) epicatechin in cocoa beans, mass and chocolate (Miller et al, 2006;Payne et al, 2010;Leite et al, 2013).…”
Section: Phenolic Compounds and Methylxantinesin Cocoa Beans During Fmentioning
confidence: 99%
“…This fact can occur since factors as genetic, soil, growing conditions and weather characteristics can affect the profile and concentration of these compounds (Niemenak et al, 2006;Meng et al, 2009;Elwers et al, 2009;Leite et al, 2013).…”
Section: Phenolic Compounds and Methylxantinesin Cocoa Beans During Fmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome the cacao production crisis caused by witches’ broom, certain Bahian farmers have invested in the gourmet chocolate market, in which flavorful cacao is worth three times the price of standard cacao. The Maranhão and Catongo (a spontaneous mutant of Comum cacao) varieties are currently used in the fine cacao market, and they have been reported to produce less astringent and more flavorful chocolate [ 17 ].…”
Section: Introductionmentioning
confidence: 99%